Heritage lost : the crisis in Canada's forest - Mackay, Donald (Toronto : Macmillan of Canada, 1985)
This book is a layman's effort to present the problem, its causes, its size and ubiquity, and how it affects people's lives, pocketbooks, and well-being, whether they work in the wood products industry or not.
Chapter 1. The forest and the trees -- Chapter 2. Hurling down the pine -- Chapter 3. "Woodman, spare that tree" -- Chapter 4. The paper forest -- Chapter 5. Cutting blind -- Chapter 6. The investigators -- Chapter 7. The regeneration gap.
Includes index.
Keywords: FOREST -- CANADA